Contemporary Zakat According to Professor Didin Hafidhuddin and Its Implementation for People's Independence - Sadzali, Akhmad; Alim, Akhmad; Mahfudz, Akhmad Affandi (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This contemporary zakat concept integrates Islamic economic principles with today's rapidly developing social and economic context. Zakat potential in Indonesia is very high, but the actual collection is still very low compared to the existing potential. Problems faced by zakat managers include a lack of awareness among Muzakki regarding zakat obligations, a zakat paradigm that is still traditional, and a lack of public trust in zakat institutions. One figure who understands the concept of zakat is Prof. Didin Hafidhuddin. Contemporary zakat implementation includes the establishment of transparent and accountable institutions for collecting and distributing zakat. Modern zakat offers relevant solutions to overcome the problems of poverty, inequality, and social injustice. Through a deeper understanding of the contemporary concept of zakat and its implementation, Muslims can contribute more effectively to achieving sustainable economic and social independence. Contemporary zakat can be used to support the independence of the people through educational programs, skills training, and the development of micro and small businesses. The research method used is a qualitative method with a descriptive approach. Observations and interviews were used to collect data. The aim of this research is to examine in depth the thoughts of Prof. Didin Hafidhuddin about contemporary zakat and its implementation for the independence of the people.